Microfluidic Platforms for the Production of Nanoparticles at Flow Rates Larger Than One Liter Per Hour. Issue 9 (3rd March 2022) - Giorello, Antonella; Nicastro, Alcides; Berli, Claudio L. A.
Abstract: The convergence of microfluidics and nanotechnology has demonstrated a synergetic potential for the preparation of advanced pharmaceutics. Nowadays, there is a renewed interest in the subject, boosted by the approval of nucleic acid‐loaded lipid‐based nanoparticles. Microfluidics enables the physical scenario to achieve well‐controlled formulations and plays an essential role in nanocarriers development; nevertheless, technical improvements are still required to reach the production rates demanded by the good manufacturing practice of the pharmaceutical industry. Here, the advances recently made to upscale the microfluidic preparation of nanoparticles are revised. The analysis was specifically focused on microfluidic methods producing liters per hour. The state‐of‐art technology has been studied after a comprehensive examination of the disclosed developments, covering both scientific papers and invention patents. An abridged overview of how the processes designed at the benchtop scale (milliliters per hour) are being translated to industrial scales (liters per hour) is also presented. Abstract : The synergetic convergence of microfluidics and nanotechnology provides unprecedented routes for the preparation of advanced pharmaceutics. Here the latest efforts made to upscale the microfluidic production of nanoparticles for drug delivery systems are examined. The microfluidic platforms that operate at flow rates larger than one liter per hour are assessed to be effectively translated to industrial production.